DIALLEL ANALYSIS OF SWEET POTATO [IPOMOEA BATATUS (L.) LAM] GENOTYPES FOR COMBINED BETA CAROTENE AND DRY MATTER CONTENT IN SOUTHERN GUINEA SAVANNA, NIGERIA. (2019) - S, Afolabi M.; Bello, Bello; B, O.; O, Agbowuro G.; Aremu, Aremu; O, C.; Akoroda, Akoroda; M.O., M.O.
No abstract available